2018
DOI: 10.1016/j.foodchem.2017.09.117
|View full text |Cite
|
Sign up to set email alerts
|

Fried potatoes: Impact of prolonged frying in monounsaturated oils

Abstract: Fresh potatoes were intermittently deep-fried up to recommended limits (175°C, 8h/day, 28h) in extra-virgin olive oil (EVOO), peanut oil (PO) and canola oil (CO), and compared for diverse chemical components and sensorial attributes, aiming to quantify the impact of prolonged frying on potatoes nutrients, and the potential alterations resulting from the use of different monounsaturated-rich oils. Independently of oil type, its degradation promotes time-dependent losses of important potato nutrients, as vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 37 publications
(54 reference statements)
12
28
0
1
Order By: Relevance
“…e results showed that all chemical qualities of oil being used to fry carbohydrateand protein-based foods increased with frying time ( Figure 5). ese are similar to a study of Santos et al [34] and Udomkun et al [35] who studied the change of frying medium during frying of potatoes and chicken nuggets, respectively. e highly linear relationship between FFA and frying time was observed (R 2 > 0.95), while polynomial correlation was found in TPMs and FOS reading (R 2 > 0.97) ( Table 2).…”
Section: Changes Of Chemical Qualitiessupporting
confidence: 89%
“…e results showed that all chemical qualities of oil being used to fry carbohydrateand protein-based foods increased with frying time ( Figure 5). ese are similar to a study of Santos et al [34] and Udomkun et al [35] who studied the change of frying medium during frying of potatoes and chicken nuggets, respectively. e highly linear relationship between FFA and frying time was observed (R 2 > 0.95), while polynomial correlation was found in TPMs and FOS reading (R 2 > 0.97) ( Table 2).…”
Section: Changes Of Chemical Qualitiessupporting
confidence: 89%
“…In particularly, alkadienals were reduced by 55% (Fig. (A)), with E , E ‐2,4‐decadienal, formed from the peroxidation of linoleic acid, as the main aldehyde. Regarding alkenals, the prominent compounds were E ‐2‐decenal, Z ‐2‐heptenal, 2‐undecenal and 2‐decenal, increasing with time (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that for all colour coordinates (L*, a* and b*) there was a degree of variability both from one samosa to another samosa and also from one side to the other side of the same samosa. This is natural, since the frying operation induces important changes in colour, which may not be equal, not even for the products submerged in the same oil (Santos, Molina-Garcia, Cunha, & Casal, 2018;J. Tian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%